IDENTIFIKASI MINAT SISWA SMP NEGERI 21 SEMARANG TERHADAP PEMBELAJARAN IPA-FISIKA BILINGUAL (UPEJ Unnes Physics Education Journal, 2013)
Bilingual use phenomenon in science-physics learning activities is still faced many challenges. This raises several issues that cause learning objectives cannot be achieved. Although science-physics bilingual lesson is not an interest-based optimal subject, based on preliminary study that has been done in SMP 21 Semarang, students have not been able to actively participate or engage optimally both mentally and actions undertaken in the learning process. The purpose of this study is to identify how the students' interest towards science-physics bilingual lesson and the factors that influence it. The result showed that students' interest in learning science-physics included in the medium category. Factors affecting the interest are classified into two: (1) internal factors, namely the will, needs and motivations, and (2) external factors:Â family support, teaching methods, relationships with teachers and other students, and the mass media